ASPECTOS RELACIONADOS AOS PARÂMETROS FISIOLÓGICOS EM MAMONA (RICINUS COMMUNIS L.) - Bandeira, Taiane P.; Juswiak, Patrícia; Diniz, Cíntia; Sauter, Anelise C.; Sauter, Fernanda K.; Dambrós, Diego; Bach, Sandro; Carbonera, Roberto; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo